Znaczenie miejsca w terapii i poradnictwie - Ładyżyński, Andrzej (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
Location where the therapy is being held constitutes a substantial, however not fully appreciated and specific factor determining the effectiveness of the process. Organization of the room in therapy depends on the therapist’s theoretical approach as well on the type of patients (individual, couple, married couple, group, adults, teenagers or children). A signboard or lack of it can be of significance as well as location of the office. The character of the therapy room depends on its organizator. Institutional offices bear more substantial marks of official character whereas the private rooms are more often arranged more tastefully. It can be noticed that room’s arrangement and its decor resembles that of one’s own house.
Keywords: counselling; therapy; place; space